Effects of fertilization with cassava residues on yield and fruit quality of tomato - Vieites, Rogério Lopes (Pesquisa Agropecuaria Brasileira, 1998)
The objective of this research was to evaluate the residue from cassava, known as "manipueira", as an alternative for tomato (Lycopersicon esculentum) fertilization. This experiment was carried out in UNESP with the cultivar Rio Grande. The experimental design was a completely randomized blocks in a 3 x 3 factorial arrangement with five blocks. Treatments constituted the following: 1) witness; 2) 54 m3/ha of "manipueira"; 3) 108 m3/ha of "manipueira"; 4) half recommended mineral fertilization; 5) half recommended mineral fertilization + 54 m3/ha of "manipueira"; 6) half recommended mineral fertilization + 108 m3/ha of "manipueira"; 7) recommended mineral fertilization; 8) recommended mineral fertilization + 54 m3/ha of "manipueira" and 9) recommended mineral fertilization + 108 m3/ha of "manipueira". Tomato yield, number of fruits per plant, fruit diameter and lenght, total soluble solids (TSS), total titratable acidity (TTA) and the ratio TSS/TTA were evaluated. The results obtained indicated that "manipueira" contributed significantly to yield and quality of pos-harvested tomato fruits.